Transient Osteoporosis in a Young Man: Case report - Case Report - Barış Nacır; Ali Yusuf Öner; Süheyl Poçan (Galenos Yayinevi, 2008)
Although osteoporosis is defined as being a painless and progressive condition, one special subtype of osteoporosis is reversible and painful. Because it isn't permanent and is obvious in the hip joint, this condition is called transient osteoporosis of the hip. Typically, the paitents are women in the third trimester of pregnancy and middle-aged men who are seen initially with acute progressive pain, antalgic gait, and severe functional disability involving the affected extremity. Its aetiology remains a matter of speculation, and the same remains true for its treatment. Many researchers have proposed different surgical and non-surgical treatment strategies; but the conservative approach, which takes the form of analgesics, intermittent traction, range of motion exercises, abductor strengthening exercises and restricted weight bearing, is preferred. In this paper we report a 22 years old man with transient osteoporosis of the hip who showed excellent recovery following a conservative approach. (From the World of Osteoporosis 2008;14:35-9)